Moral Values of Rahwana’s Figure in Rahwana Putih Novel by Sri Teddy Rusdy - Wiekandini Dyah Pandanwangi (Jurnal Lingua Idea, 2020)
Rahwana Putih, a novel by Sri Teddy Rusdy, reveals the figure of Rahwana with good characters and behaviours. The characters appeared contain moral values that can be considered as a role model. This phenomena is interesting to be explored deeply because, here, Rahwana is presented differently from its stereotype in all puppet stories. Based on this research background, this study aims to analyze moral values contained in Rahwana Putih by Sri Teddy Rusdy. Structuralism approach is used to analyze the moral values on Rahwana figure which emphasizes on intrinsic elements of fiction works. The MacIntyre’s theory of morality that cores on truthfulness and trust, justice, and courage is also applied to observe these values. The method used in this study is analytical descriptive and it consists of primary and secondary data sources. The primary data source is Rahwana Putih by Sri Teddy Rusdy, while the secondary data sources are journals and references which are relevant to the research problem. The techniques for collecting data comprise reading, classifying, reducing and describing data. The technique used to analyze the data is content analysis. The results show that the moral values appeared in Rahwana’s characters embrace honesty, trust, justice and courage are the manifestation of Javanese leadership concept called astabrata.